Effect of Undergraduate Research Output on Faculty Scholarly Research Impact - Popescu, Adriana; Popescu, Radu (Evidence Based Library and Information Practice, 2017)
Objective – In the context of the ongoing discourse about the role of Institutional Repositories (IRs), the objective of the study is to investigate if there is any evidence of a relation between undergraduate student activity in an IR and the impact of faculty research.Methods – The data used for the study is representative of six academic departments of the College of Science and Mathematics (CSM) at California Polytechnic State University (Cal Poly). Digital Commons@Cal Poly (DC) is the IR supported by the library. Regression analysis was used to investigate the interdependence between faculty research impact (dependent variable) and undergraduate student repository activity (independent variable). For each department, faculty research impact was quantified as a measure of the citation counts for all faculty publications indexed in Web of Science (WoS) between January 2008 and May 2017. Student repository activity was quantified for each department in two ways: (1) total number of student projects deposited in DC since 2008 (Sp) and (2) total number of student project downloads from DC (Sd). The dependent variable was regressed against each of the two elements of student repository activity (Sp and Sd), and the resulting statistics (sample correlation coefficients, coefficients of determination, and linear regression coefficients) were calculated and checked for statistical significance.Results – The statistical analysis showed that both components of student repository activity are positively and significantly correlated with the impact of faculty research quantified by a measure of the citation counts. It was also found that faculty repository activity, although positively correlated with faculty research impact, has no significant effect on the correlation between student repository activity and faculty research impact.Conclusion – The analysis considers two distinct groups of publications: one group of student publications (senior projects) from six academic departments, which are deposited in an open repository (DC), and one group of publications (not necessarily represented in DC) of faculty affiliated with the same six departments and whose citation impact is believed to be affected by the first group. The statistical correlation between student repository activity and faculty research impact can be seen as an indication that an active, open IR centered on collecting, preserving, and making discoverable student research output has a positive impact on faculty’s research impact. More research that includes additional factors and uses a larger data set is necessary to arrive at a definitive conclusion.